Description of Submission of Claim Files Inpatient Health BPJS at Kolonel Abundjani RSD Bangko - Hendry Bowo Wibowo (Universitas Veteran Bangun Nusantara, 2021)
Based on preliminary observation at RSD Kolonel Abundjani Bangko in early August 2020, the submission of claim file was implemented well. In submission of BPJS claims file Inpatient health has been delayed due to limited coding officers and sometimes incomplete files. The purpose of this study was to find out the description of submission of BPJS claim inpatient health file at RSD Kolonel Abundjani Bangko.The research was conducted in RSD Kolonel Abundjani Bangko by using descriptive method. Technique of collecting data by observation and intervie. From the results of the study showed that the claim file originated from the place of admission to the hospital which later to the treatment room. When the patient comes home, the file is taken directly to the medical record to be coded, grouper and in-input. Then in submission of claims file to BPJS Health must be accompanied by the news event files and txt-shaped files.The conclusion of this research is the procedure of submission of BPJS claims file of inpatient health starting from the place of admission to the ward or the treatment room, after the patient returns the file directly taken to the medical record for dicoding, gruper, and input. Then the file is submitted to the BPJS Hospital health section to be verified by using file event files and txt-shaped files. Officers who receive BPJS health care claim file are medical record-keeping officers Standard time in submission of BPJS claims file Inpatient health in RSD Kolonel Abundjani Bangko is 2 x 24 hours since patient leave hospital.